Dynamics from open innovation to evolutionary change - JinHyo Joseph Yun; DongKyu Won; Kyungbae Park (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
We created conceptual models that people may use to analyze and forecast the dynamic effects of open innovation, which we applied to the smartphone sector using a model-based analysis approach. In addition, we built an open innovation simulation model for the smartphone sector. The dynamic model of open innovation linked logic and concepts relating to open innovation, complex adaptive systems, and evolutionary change. The model can be used to analyze the dynamic effects of open innovation strategies and open innovation simulation for the selection of future strategies.
Keywords: 650; Open innovation; Complex adaptive system; Evolutionary change; Smartphone